Physical activity, sedentary time and sleep in cystic fibrosis youth: A bidirectional relationship?. Issue 2 (8th December 2020) - McNarry, Melitta A.; Stevens, Daniel; Stone, Michelle; Roberts, Spencer; Hall, Sarah; Mackintosh, Kelly A.
Abstract: Purpose: Physical activity (PA) and sleep are highly important for those with cystic fibrosis (CF), yet, despite this and suggestions of a bidirectional relationship between these factors in healthy children, their relationship is yet to be investigated. Methods: PA, sedentary time (SED), and sleep were objectively derived over seven days in 58 youth (11.9 ± 2.7 years; 29 CF). Generalized linear latent and mixed models with a random intercept and slope at child‐level were adjusted for age, sex, wear‐time, type of day, group and mean PA/SED and sleep. Results: Every additional 10 min sedentary was associated with 5.6 and 5.0 min less sleep and 10.6 and 12.0 min less wake after sleep onset (WASO) that night, in CF and healthy children, respectively. PA, regardless of intensity, was not associated with total sleep time but every additional 10 min of light PA (LPA) was associated with 3.0 min less WASO in healthy participants. Ten mins more sleep was associated with 3.1 and 1.7 min less SED in CF and healthy children, respectively. In CF, greater sleep time led to less LPA (3.6 min) the following day, whereas, in healthy children, poor sleep quality (greater WASO) was associated with more LPA (1.4 min) and moderate‐to‐vigorous PA (5.2 min) the following day. Conclusion: A bidirectional relationship between SED and subsequent total sleep time was evident, irrespective of group, whereas the relationship between sleep and PA was group dependent. These findings have important implications regarding the reciprocal effects of promoting PA or sleep quantity or quality.